Cartilage adhesive and mechanical properties of enzymatically crosslinked polysaccharide tyramine conjugate hydrogels1. (14th April 2014) - Wang, R.; Leber, N.; Buhl, C.; Verdonschot, N.; Dijkstra, P. J.; Karperien, M.; Katzhendler, Joshua; Domb, Abraham J.
<x xml:space="preserve">Abstract</x> Using a home‐built tensile tester, adhesion and mechanical properties of injectable enzymatically crosslinkable hydrogels were determined by placing the hydrogels in between cartilage surfaces. Dextran–tyramine (Dex‐TA) and hyaluronic acid–tyramine (HA‐TA) conjugates as well as a 50/50 composite material of these polysaccharide conjugates were tested. To integrate the injectable hydrogels with the cartilage tissue, pretreatment of the tissue with a Dex‐TA conjugate solution strongly improved the adhesion. Only failure of the crosslinked hydrogel was observed and not at the hydrogel–tissue interface. Moduli of a Dex‐TA hydrogel are higher than those of a HA‐TA hydrogel, whereas the ultimate strain of the HA‐TA hydrogel was at least three times higher. The Dex‐TA/HA‐TA hydrogel has similar storage and elastic moduli as the Dex‐TA gel and also an ultimate strain of ~30%, similarly as found for the HA‐TA gel. The controlled biodegradability and gelation time of the Dex‐TA/HA‐TA hydrogel, the developed method for strong tissue adhesion of the gel particularly in comparison with fibrin glue, makes this material applicable as an injectable hydrogel for tissue regeneration applications. Copyright © 2014 John Wiley & Sons, Ltd.